Pengaruh Kepuasan Kerja dan Motivasi Kerja Terhadap Produktivitas Kerja Karyawan Di Wisata Cafe Sawah Pujon Kidul - Sihabussina (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
The research was conducted to determine the effect of the variables studied, namely job satisfaction and work motivation on employee work productivity in the Pujon Kidul rice field café tour. Quantitative method is a method used with the causality approach. The object of this research is employees, amounting to 90 people. As for processing the data, researchers used various kinds of tests, namely validity, reliability, classical assumptions, and hypotheses. Based on the test results, partially the variables X1 and X2 have a significant positive effect on employee work productivity, both simultaneously and the variable X has a significant positive effect on variable Y in the study. Keywords: Job Satisfaction; Work Motivation; Work Productivity